Identification of distinct haemocyte populations from the freshwater bivalves swan mussel (Anodonta cygnea) and duck mussel (anodonta anatina) using wheat-germ agglutinin - Hinzmann M. (2017)
Haemocytes play a major role in molluscs immunity. Functional studies are, however, impaired by limited available experimental tools to identify and sort distinct haemocyte populations. Therefore, using nonlethal methods, we aimed at evaluating whether lectin staining combined with flow cytometry could be used to distinguish circulating haemocyte populations from two freshwater bivalves of the family Unionidae, the duck mussel (Anodonta anatina (L., 1758)) and the swan mussel (Anodonta cygnea (L., 1758)). Based on classical classification, haemocytes were distinguished as granulocytes and hyalinocytes and cytological features were visualized using transmission microscopy and staining techniques. Size, granularity, viability, and surface staining using lectins as specific probes were analysed by flow cytometry and fluorescence microscopy. The microscopic proportions of granulocytes and hyalinocytes significantly differed, being of 70% and 30% for A. cygnea and of 85% and 15% for A. anatina, respectively. Two haemocyte populations were sorted by flow cytometry based on size and granularity and confirmed as granulocytes and hyalinocytes. Interestingly, two different granulocyte populations could be further discriminated in A. cygnea according to their binding affinity to wheat-germ agglutinin (WGA), whereas granulocytes of A. anatina all stained similarly. Our results show that WGA labelling combined with flow cytometry can be used to better discriminate Anodonta haemocyte populations and obtain purified populations for functional studies. © 2017, Canadian Science Publishing. All rights reserved.